Desa Kreatif Kelola Sampah Organik dan Anorganik (Desa Relasi): Pemanfaatan Sampah dan Pemberdayaan Masyarakat Desa Tegal Sari - Ihya Hazairin Noor; Ahmad Saipullah; Lutfhi Hana; Madinatul Agniya Ilma; Maurent Carolin Bolang (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
Background: Waste that continues to accumulate every year is an unresolved environmental problem at the regional to global level. This problem can actually be overcome by applying good waste management according to its type (organic and inorganic). However, waste management is still rarely practiced in the community, for example for residents of Tegal Sari Village RT 1 and 3, Satui District, Tanah Bumbu Regency. The waste segregation, disposal, and processing system in the village is not optimal. Objective: Therefore, the Desa Relasi program aimed to increase the knowledge and awareness of residents in managing organic and inorganic waste through Takakura composting and inorganic crafts. Methods: The program was formed based on the results of problem priorities obtained during PBL through identification and analysis of health problems in the village by collecting secondary and primary data (with interviews and questionnaires). Results: Activities in the program are in the form of counseling, cadre debriefing, demonstration, and practice. The evaluation instruments used were pre-post test questionnaires (I and II), observation, and evaluation through chat. Based on the results of the knowledge test during counseling, 72.73% of residents experienced an increase in knowledge, 22.73% were stagnant, and 4.55% experienced a decrease (pre-post test I). While in post-test I - II, 77.72% experienced an increase, 18.18% did not experience an increase or decrease, and 4.55% experienced a decrease. Conclusion: There was an increase in knowledge in most participants regarding organic and inorganic waste management. Therefore, it is hoped that Tegal Sari Village residents will be able to apply good waste management so that it can produce use, sale and aesthetic value and advance the village.